Mining expertise of developers from software repositories. (10th April 2020) - Hammad, Maen; Hijazi, Haneen; Hammad, Mustafa; Otoom, Ahmed Fawzi
This paper presents a technique to mine the developers' contributions to explore their expertise in open source projects. The technique analyses the keywords that appear in the textual content of commits. It is a lightweight technique since the text in commits is analysed without making any syntactic code differencing. Each developer is linked with a list of keywords, with their frequencies, that appeared in his commits. Based on these keywords, three types of expertise are defined: unique, common and frequent. The identified expertise can help in identifying topics or issues that are handled by specific or group of developers. A tool is developed to automatically mine and analyse committed code changes to support expertise identification. A case study is presented on three open source projects to show how the proposed techniques can be applied. The observations of the study showed that frequent terms provide useful information about developers' expertise.